Budget Rigidity and Expenditure Efficiency in Slovenia - Mattina, Todd (IMF Working Papers; Working Paper ;, 2007)
This paper assesses the relative efficiency and flexibility of public spending in Slovenia compared to the advanced and new EU member states. Spending on health care, education, and social protection is relatively high in Slovenia without achieving correspondingly better outcomes. Inefficiencies appear to stem from the financing mechanisms for social services, institutional arrangements, and the weak targeting of social benefits. In addition, the composition of spending appears to be strongly tilted towards nondiscretionary items that reduce the fiscal room for maneuver. Greater flexibility is needed to facilitate the reallocation of relatively inefficient expenditure into higher priorities. In this manner, medium-term expenditure rationalization can focus on reducing inefficient outlays rather than restraining traditionally flexible components of the budget, such as public investment.